Plant food allergens: peach non-specific lipid transfer protein Pru p 3 as a model. A review - Salcedo, G.; Sánchez-Monge, R.; Díaz-Perales, A. (Spanish Journal of Agricultural Research, 2008)
Plant non-specific lipid transfer proteins (LTPs) are plant defence proteins that constitute a relevant panallergen family present in both plant foods and pollens. Their high resistance to proteolytic digestion, thus being probably primary sensitizers by ingestion, and association with systemic and severe clinical symptoms, have led to propose LTPs as a model of true food allergens. Peach Pru p 3, the prototypic member of the family, has been extensively studied at the biochemical, immunological and clinical level. IgE-binding regions of Pru p 3 have been identified by an experimental and modelling based approach.